Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1954
DOI: 10.1063/1.1721664
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a Vapor Bubble in a Superheated Liquid

Abstract: The integro-differential equation for the growth of a vapor bubble in a superheated liquid is formulated and discussed. It is shown that two distinct time domains exist: one, of the order of 10−4 second, during which the effect of the hydrodynamic forces may be an important factor in the growth of the bubble, and another, during which this effect is unimportant. An integral equation is formulated for the latter domain. A solution of the problem, in closed form, valid for the entire interval of interest is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
0

Year Published

1955
1955
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(134 citation statements)
references
References 3 publications
12
122
0
Order By: Relevance
“…Numerous studies have been conducted over the past 50 years to understand the formation of vapor bubble. [4][5][6][7][8] Some of these studies investigated the physics of bubble formation and controlling the size of the bubble in microscale devices using micro-resistive heaters. 7,8 In recent years, vapor bubble actuated by laser has attracted considerable interest.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…Numerous studies have been conducted over the past 50 years to understand the formation of vapor bubble. [4][5][6][7][8] Some of these studies investigated the physics of bubble formation and controlling the size of the bubble in microscale devices using micro-resistive heaters. 7,8 In recent years, vapor bubble actuated by laser has attracted considerable interest.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…In this case, the bubble radius increases as a linear function of time. The large time solution is governed by heat and mass transfer, and has been studies by Plesset & Zwick (1954), Forster & Zuber (1954), Striven (1959) and Bankoff (1964). The bubble radius then follows a square root dependence of the time.…”
Section: Nucleation and Supersaturation In Gas-liquid And Vapouriiquimentioning
confidence: 99%
“…Pies set and Zwickvl9) and Forster and Zuber (20) have shown that in a superheated liquid the bubble growth rate, including the effect of heat diffusion across the bubble wall, exhibits the following behavior:…”
Section: Fundamental Equations and Parametersmentioning
confidence: 99%